Heparins Sourced From Bovine and Porcine Mucosa Gain Exclusive Monographs in the Brazilian Pharmacopeia - Vilanova, Eduardo; Vairo, Bruno C.; Oliveira, Stephan-Nicollas M. C. G.; Glauser, Bianca F.; Capillé, Nina V.; Santos, Gustavo R. C.; Tovar, Ana M. F.; Pereira, Mariana S.; Mourão, Paulo A. S. (Frontiers in Medicine, 2019)
Most of the unfractionated heparin (UFH) consumed worldwide is manufactured using porcine mucosa as raw material (HPI); however, some countries also employ products sourced from bovine mucosa (HBI) as interchangeable versions of the gold standard HPI. Although accounted as a single UFH, HBI, and HPI have differing anticoagulant activities (~100 and 200 IU mg−1, respectively) because of their compositional dissimilarities. The concomitant use of HBI and HPI in Brazil had already provoked serious bleeding incidents, which led to the withdrawal of HBI products in 2009. In 2010, the Brazilian Pharmacopeia (BP) formed a special committee to develop two complementary monographs approaching HBI and HPI separately, as distinct active pharmaceutical ingredients (APIs). The committee has rapidly agreed on requirements concerning the composition and presence of contaminants based on nuclear magnetic resonance and anion-exchange chromatography. On the other hand, consensus on the anticoagulant activity of HBI was the subject of long and intense discussions. Nevertheless, the committee has ultimately agreed to recommend minimum anti-FIIa activities of 100 IU mg−1 for HBI and 180 IU mg−1 for HPI. Upon the approval by the Brazilian Health Authority (ANVISA), the BP published the new monographs for HPI and HBI APIs in 2016 and 2017, respectively. These pioneer monographs represent a pivotal step toward the safest use of HBI and HPI as interchangeable anticoagulants and serve as a valuable template for the reformulation of pharmacopeias of other countries willing to introduce HBI.